2015
DOI: 10.5152/kd.2014.30
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Health Personnel Towards People Living With HIV

Abstract: Objective: The objectives of this study were to find out the level of prejudice amongst doctors and nurses against people living with HIV (PLHIV) at a teaching and research hospital, and to determine the underlying factors of this prejudice. Methods: A 39-question survey was applied to 126 doctors and nurses in order to determine the demographic characteristics of participants and to measure the level of disease knowledge and level of prejudice against PLHIV. Correlation was found between participants' demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
2
3
0
4
Order By: Relevance
“…The overall wellbeing of HIV-infected patients who delay or avoid medical care has been impaired as indicated by these studies (10,11) This study was conducted in three hospitals in Istanbul, Turkey. Comparing the results of this study to others conducted in Turkey, it is seen that the outcomes are similar (12,13). The level of knowledge of hospital workers regarding HIV was mostly insufficient.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The overall wellbeing of HIV-infected patients who delay or avoid medical care has been impaired as indicated by these studies (10,11) This study was conducted in three hospitals in Istanbul, Turkey. Comparing the results of this study to others conducted in Turkey, it is seen that the outcomes are similar (12,13). The level of knowledge of hospital workers regarding HIV was mostly insufficient.…”
Section: Discussionsupporting
confidence: 69%
“…This approach has been shown to lead to the avoidance of seeking healthcare by PLHIV (10,11). Studies conducted in Turkey and abroad have shown that there is indeed a lack of knowledge amongst nurses and physicians regarding HIV (12)(13)(14)(15)).…”
mentioning
confidence: 99%
“…Önermelerden alınan puan arttığında, bilgi ve damgalama düzeyinin yüksek olduğu kabul edildi. Bilgi ve damgalama önermelerini oluşturma sürecinde, kapsamlı bir literatür taraması yapıldı [13][14][15][16][17] ve 45 önermeden oluşan bir önerme havuzu oluşturuldu. Önermelerin kapsam geçerliliğini değerlendirmek için, önermeler ve genel anket hakkındaki görüşler için 4 psikiyatri uzmanı, 4 enfeksiyon hastalıkları uzmanı ve 2 hemşire olmak üzere toplam 10 uzma-…”
Section: Hiv/aids Ile Ilgili Bilgi Ve Damgalama Düzeyini Değerlendirmunclassified
“…However, discrimination-related obstacles in accessing such services remain. For instance, the low level of knowledge about HIV infection and a high level of prejudice among medical personnel against people living with HIV (PLHIV) [53] might still be acting as a disincentive for patients to apply for testing or to start and continue treatment. This is an expected outcome, as medical education in Turkey does not cover sexual and reproductive health issues from a rights-based perspective.…”
Section: The Prevention and Treatment Of Stismentioning
confidence: 99%